A novel approach to remove outliers for parallel voice conversion. (November 2019) - Shah, Nirmesh J.; Patil, Hemant A.
Abstract: Alignment is a key step before learning a mapping function between a source and a target speaker's spectral features in various state-of-the-art parallel data Voice Conversion (VC) techniques. After alignment, some corresponding pairs are still inconsistent with the rest of the data and are considered outliers. These outliers shift the parameters of the mapping function from their true value and hence, negatively affect the learning of mapping function during the training phase of the VC task. To the best of the authors' knowledge, the effect of outliers (and hence, their removal) on quality of the converted voice has not been much explored in the VC literature. Recent research has shown the effectiveness of the outlier removal as a pre-processing step in the VC. In this paper, we extend this study with a detailed theory and analysis. The proposed method uses a score distance that is estimated using Robust Principal Component Analysis (ROBPCA) to detect the outliers. In particular, the outliers are determined using a fixed cut-off on the score distances, based on the degrees of freedom in a chi-squared distribution, which is speaker-pair independent. The fixed cut-off is due to the assumption that the score distances follow the normal (i.e., Gaussian) distribution. However, this is a weak statistical assumption even in the cases where quite many samples are available. Hence, in this paper, we propose to explore speaker-pair dependent cut-offs to detect the outliers. In addition, we have presented our results on two state-of-the-art databases, namely, CMU-ARCTIC and Voice Conversion Challenge (VCC) 2016 by developing various state-of-the-art methods in the VC. In particular, we have presented the effectiveness of the outlier removal on Gaussian Mixture Model (GMM), Artificial Neural Network (ANN), and Deep Neural Network (DNN)-based VC techniques. Furthermore, we have presented subjective and objective evaluations using a 95% confidence interval for the statistical significance of the tests. We obtained an average 0.56% relative reduction in Mel Cepstral Distortion (MCD) with the proposed outlier removal approach as a pre-processing step. In particular, with the proposed speaker-pair dependent cut-off, we have observed relative improvement of 12.24% and 30.51% in the speech quality, and 39.7% and 4.27% absolute improvement in the speaker similarity for the CMU-ARCTIC and the VCC 2016, respectively.